Measuring Enterprise Architecture / Siti Fatimah Azzahra Ibrahim - Ibrahim, Siti Fatimah Azzahra (2016)
Enterprise Architecture (EA) is an investment for organizations as it is beneficial for them. Therefore measuring is needed to be done in order to realize the EA benefits. In Malaysia, EA is relatively a new initiative for Malaysian organization to be able to compete with other organizations in order to sustain in dynamic business environment. Organizations believe that by adopting EA in their organization will help them in aligning their business process with IT. Therefore the worth of EA that is said to be delivered needed to be measured. Although the measurement is considered as one of the important evaluation needed to be done, there are not many is done in Malaysia on reasons of the limitation in EA knowledge and the acceptance of changes by employees. Case study in this research is carried out in the Ministry of Finance Malaysia (MOF) where the process of the implementation is based on their business process aligning with IT and it is not done entirely according to the theory of EA implementation. An interview session is conducted with the Business Relationship Manager (BRM) in MOF who is responsible in ensuring the information regarding EA implementation and the EA concept is understood in the organization. The data gathered assisted in identifying measuring elements that visualize the worth of the EA value. The elements are classified according to four benefit indicators; communication value, strategic value, tactical value, governance value. A draft of an evaluation model is constructed based on the literature reviewed. Measuring elements for MOF are generated after analyzing data that have been gathered from the interview session. The elements are then mapped onto the draft of the evaluation model constructed earlier. As a result, a synthesized model for measuring EA is constructed. There are limitations faced when conducting this research. However, this research will only focus on classifying measuring elements according to the four benefit indicators mentioned. By classifying these elements will assist academician as well as practitioner in measuring EA. For future work, it would be recommended for the measuring elements in the synthesized model of MOF to be used in measuring EA in MOF.